An iron-molybdenum-aluminum-nickel catalyst for the synthesis of polyetheramines and its preparation process

By using iron-molybdenum aluminum-nickel metal alloy as catalysts, the problems of low catalytic activity, insufficient structural strength and short life of the existing catalysts are solved, and efficient and long-life polyetheramine synthesis effect is achieved.

CN116764642BActive Publication Date: 2025-02-07SHANDONG LONGHUA CHEM TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310758051.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2025-02-07
Estimated Expiration
2043-06-26

AI Technical Summary

Technical Problem

The existing catalysts used for polyetheramine synthesis have problems such as low catalytic activity, insufficient structural strength and short life. In particular, the supported catalysts are prone to lose surface holes due to rolling friction during use, resulting in permanent inactivation.

Method used

Using iron-molybdenum aluminum-nickel metal alloy as catalyst, by adjusting the content and structure of nickel, aluminum, molybdenum and iron in the alloy, a catalyst with high pore volume and bulk density is formed, avoiding the additional use of porous support, and improving the selectivity of the catalyst and efficiency.

Benefits of technology

The effects of high catalytic activity, high structural strength and long service life are achieved, and the problem of inactivation of the catalyst due to surface collapse during use is avoided, and the efficiency and product quality of polyetheramine synthesis are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116764642B_ABST
    Figure CN116764642B_ABST
Patent Text Reader

Abstract

A nickel-iron-molybdenum-aluminum-nickel catalyst for the synthesis of polyetheramines and its preparation process are disclosed, belonging to the field of metal catalyst technology. The catalyst is characterized by being a monolithic metal alloy of nickel, aluminum, molybdenum, and iron, with a pore volume of 0.05 m³. 2 The catalyst has a bulk density of 2 g / ml and contains 77.3 wt%–80.7 wt% nickel, 13.6 wt%–17.7 wt% aluminum, 2.9 wt%–3.9 wt% molybdenum, and 1.2 wt%–2.6 wt% iron. The process involves: smelting nickel, aluminum, molybdenum, and iron powders twice to obtain a catalyst precursor; then reacting the precursors with sodium hydroxide aqueous solutions of different concentrations and washing the alloy particles to obtain the final product. This invention offers higher structural strength and a longer service life. The preparation process of this invention can obtain an alloy crystal phase with higher catalytic activity and can prevent catalyst collapse during the etching of larger pores, ensuring the strength of the catalyst framework.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses an iron-molybdenum-aluminum-nickel catalyst for synthesizing polyetheramine and a preparation process thereof, belonging to the technical field of metal catalysts. Background Art

[0002] Polyetheramines (PEA) are polymers with a polyether backbone and amine-terminated reactive functional groups. Polyetheramines are typically obtained by amination of polyethers under high temperature and pressure. By selecting different polyoxyalkylene structures, a range of properties, including reactivity, toughness, viscosity, and hydrophilicity, can be adjusted. The amine groups enable polyetheramines to react with a wide range of compounds. Their unique molecular structure endows polyetheramines with excellent overall properties, leading to their widespread application in a wide range of applications, including polyurea spray coatings, large-scale composite material fabrication, epoxy resin curing agents, and automotive gasoline detergents.

[0003] In the production of polyetheramines, catalyst life is generally limited by two factors. First, the pores on the catalyst surface become clogged by polyether polyols due to long-term use, reducing the catalyst's catalytic activity. This necessitates cleaning the catalyst with sodium hydroxide solution to reopen the clogged pores and maintain catalytic activity. Second, the pore structure on the catalyst's outer surface collapses due to the tumbling friction of the catalyst, eventually breaking off into powder and falling off. This depletes the catalyst's surface pores, resulting in reduced or even inactive catalytic activity. Currently, most catalysts used in polyetheramine synthesis utilize a porous support with an active component. These supported catalysts have low structural strength, resulting in a short catalyst lifespan and a high risk of permanent deactivation, as described in the second scenario.

[0004] For example, Chinese patent CN116284738A discloses a method for preparing polyetheramines, which uses an alkylphenol-formaldehyde resin polyether as a raw material and undergoes a hydroamination reaction to prepare the polyetheramines. This method uses a NiCu-supported catalyst, which suffers from a short catalyst life.

[0005] U.S. Patent No. 20230174714A1 discloses a supported catalyst for the synthesis of polyetheramines. While this supported catalyst improves the reactivity and selectivity of the catalyst by introducing metallic Mo and CeO2 into the Ni and Cu active components, it is still prepared by an isometric impregnation method in which the active components are adsorbed onto a porous alumina support. This inevitably results in low catalyst strength and a short lifespan. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a pure metal type iron-molybdenum-aluminum-nickel catalyst for polyetheramine synthesis with high catalytic activity, high structural strength and long service life and a preparation process thereof.

[0007] The technical solution adopted by the present invention to solve the technical problem is: the iron-molybdenum-aluminum-nickel catalyst for the synthesis of polyetheramine is characterized in that the catalyst as a whole is a metal alloy of nickel, aluminum, molybdenum and iron, and the pore volume of the catalyst is 0.051m 2 / g~0.055m 2 / g, the bulk density is 1.95g / ml~2.13g / ml, the nickel content in the catalyst is 77.3wt%~80.7wt%, the aluminum content is 13.6wt%~17.7wt%, the molybdenum content is 2.9wt%~3.9wt%, and the iron content is 1.2wt%~2.6wt%.

[0008] The invented catalyst is a pure metal catalyst with enhanced structural strength and a long service life. It eliminates the need for an additional porous carrier, resulting in enhanced catalytic activity. The catalyst controls pore volume, ensuring smooth flow of polyether polyol, liquid ammonia, and hydrogen through the catalyst surface pores, thereby improving the utilization rate of the active ingredients. The catalyst also adjusts the amount of the alloy's heavy metal components, adding a specific ratio of molybdenum and iron. This not only improves the catalyst's selectivity and efficiency, but also enhances its overall strength and extends its service life.

[0009] Preferably, the crystal grain diameter of the metal crystal phase in the catalyst is 1nm to 3nm, the skeleton strength of the catalyst is 161N / cm to 168N / cm, and the specific surface area of ​​the catalyst is controlled within the range of 10m 2 / g~30m 2 / g.

[0010] The specific surface area of ​​the catalyst of the present invention is controlled within the range of 10m 2 / g~30m 2 / g. In theory, the larger the specific surface area of ​​the catalyst, the higher the catalytic activity. However, in the production process of polyetheramine, the catalyst is fixed to the reactor wall in a fixed bed. When the specific surface area of ​​the catalyst increases, the corresponding catalyst surface voids become smaller, and the possibility of the catalyst surface voids through which the polyether polyol, liquid ammonia and hydrogen flow decreases, which in turn has an adverse effect on the reaction. Therefore, after data comparison, when the specific surface area of ​​the catalyst is 10m 2 / g~30m 2 / g has the highest catalytic performance.

[0011] A preparation process of the above-mentioned iron-molybdenum-aluminum-nickel catalyst for polyetheramine synthesis is characterized in that the process steps are:

[0012] Prepare nickel, aluminum, molybdenum, and iron metal powders in a mass ratio of 62-68:27-33:2.3-3.3:1.45-1.85;

[0013] 1) Heat the aluminum powder to 695-710°C, melt it, and keep it warm for 270-400 seconds. Then heat it to 990-1020°C, add nickel powder, and stir it evenly with a carbon rod within 600 seconds.

[0014] 2) Using the self-heating generated by nickel dissolution to raise the furnace temperature by 200°C to 300°C, then heating to 1449°C to 1459°C, and keeping the temperature for 18min to 26min;

[0015] 3) Cooling the melt to room temperature within 300 seconds to obtain a nickel-aluminum alloy;

[0016] 4) heating the nickel-aluminum alloy to 1449° C. to 1459° C., melting the alloy, adding molybdenum powder and iron powder, and stirring the mixture evenly with a carbon rod for 600 seconds; then maintaining the temperature for 55 to 65 minutes, and cooling the mixture to room temperature within 300 seconds to obtain an aluminum-nickel-molybdenum-iron alloy, i.e., a catalyst precursor;

[0017] 5) Crushing the prepared catalyst precursor to obtain alloy particles, adding an 8 wt% to 13 wt% sodium hydroxide aqueous solution to the alloy particles, gradually increasing the temperature from 10° C. to 105° C., and reacting until no obvious bubbles emerge from the alloy particles, and then filtering;

[0018] 6) After filtering out the alloy particles, add 18 wt% to 23 wt% sodium hydroxide aqueous solution, and gradually increase the temperature from 25° C. to 80° C., and maintain the reaction until the alloy particles sink to the bottom and no obvious bubbles emerge. Filter and wash the alloy particles to obtain the catalyst for polyetheramine.

[0019] The metal catalyst of the present invention is prepared through two smelting steps followed by pore formation. Aluminum is first melted to a specific flow state, after which nickel powder is added. After uniform mixing in this state, the mixture is heated to the smelting temperature, resulting in a special state of nickel-aluminum molten alloy mixed with the aluminum. This alloy is then rapidly cooled to form a nickel-aluminum crystalline alloy. This alloy is then heated again to the smelting temperature, followed by the addition of molybdenum and iron. After smelting, a complex crystalline phase of the four metals is formed in the catalyst. The presence of nickel-molybdenum, nickel-iron, and other crystalline phases not only improves the selectivity of the catalyst but also significantly enhances its skeletal strength. During the catalyst pore formation process, the present invention aims to produce a catalyst with a larger pore size and higher strength. The present invention first uses a low-concentration sodium hydroxide solution to react with the aluminum in the alloy, etching holes with a depth of 3 to 5 mm in the catalyst precursor. Then, a slightly higher-concentration sodium hydroxide solution is used for more thorough etching, resulting in a hole depth of 5 to 7 mm. The two etching steps create larger pores in the catalyst, thereby controlling the gas escape rate, preventing gas explosions from cracking the catalyst body, and effectively preventing the catalyst from collapsing during the pore formation process, thereby maintaining the catalyst's skeletal strength.

[0020] Preferably, in the above-mentioned process for preparing the iron-molybdenum-aluminum-nickel catalyst for polyetheramine synthesis, the mass ratio of the nickel, aluminum, molybdenum, and iron metal powders is 64-66:29-31:2.6-3.0:1.60-1.70. This preferred ratio of metal powders results in a more balanced pore distribution after etching, with pore diameters that maximize specific surface area while minimizing clogging, resulting in higher catalytic activity and a stronger catalyst skeleton.

[0021] Most preferably, the mass ratio of the nickel, aluminum, molybdenum, and iron metal powders is 65.55:30:2.8:1.65. This most preferred ratio achieves the best catalytic effect and longer service life of the catalyst of the present invention.

[0022] Preferably, in the preparation process of the iron-molybdenum-aluminum-nickel catalyst for polyetheramine synthesis, the particle sizes of the metal powders are: nickel powder 2μm-5μm, aluminum powder 8μm-14μm, molybdenum powder 5μm-8μm, and iron powder 5μm-8μm. Nickel powder is the finest, while aluminum powder is the coarsest. This is because the coarseness of aluminum powder is proportional to the pore size of the catalyst obtained after the catalyst is finally washed with sodium hydroxide solution. However, the larger the aluminum powder particle size, the lower the strength of the catalyst skeleton after the sodium hydroxide solution is washed. The addition of iron and molybdenum powders can effectively enhance the catalyst skeleton strength, preventing damage to the catalyst surface caused by collisions during later use, and extending the catalyst's service life from the conventional three years. The catalyst produced with the optimal particle size combination exhibits better catalytic performance and a higher conversion rate in the polyether-to-polyetheramine reaction.

[0023] Preferably, in the above-mentioned preparation process of the iron-molybdenum-aluminum-nickel catalyst for polyetheramine synthesis, the cooling method described in step 3) and step 4) is to place the melt inside or outside a cooling tank and cool it down using flowing cooling water.

[0024] Preferably, in the above-mentioned process for preparing the iron-molybdenum-aluminum-nickel catalyst for polyetheramine synthesis, nitrogen is purged throughout the heat preservation and melting process described in step 2) and step 4). Nitrogen protection during the melting process prevents metal oxidation and ensures safety of the preparation.

[0025] Preferably, in the above-described process for preparing an iron-molybdenum-aluminum-nickel catalyst for polyetheramine synthesis, the alloy particles obtained in step 5) are irregular particles with a particle size of 10 mm to 25 mm. With these preferred alloy particles, the etching depth of the present process can better utilize the active components within the catalyst while also maintaining a high skeleton strength.

[0026] Preferably, in the above-mentioned process for preparing the iron-molybdenum-aluminum-nickel catalyst for polyetheramine synthesis, the mass ratio of the alloy particles to the sodium hydroxide contained in the sodium hydroxide aqueous solution in step 5) is 5:0.8-1.3; and the mass ratio of the alloy particles to the sodium hydroxide contained in the sodium hydroxide aqueous solution in step 6) is 5:1.7-2.4. By controlling the amount of sodium hydroxide used, the degree of aluminum reaction in the alloy and the depth of the pores can be controlled, thereby better ensuring the activity and skeletal strength of the catalyst.

[0027] Preferably, in the above-mentioned process for preparing the iron-molybdenum-aluminum-nickel catalyst for polyetheramine synthesis, the washing step 6) comprises decantation of the filtered alloy particles with pure water four times, spray washing until the pH of the water is neutral, and then decantation three times with 95% ethanol; the resulting polyetheramine catalyst is stored in pure water or ethanol for future use. This preferred washing process ensures thorough cleaning of the catalyst, meeting the catalyst's usage requirements.

[0028] Compared with the prior art, the beneficial effects of the iron-molybdenum-aluminum-nickel catalyst for the synthesis of polyetheramines and the preparation process thereof of the present invention are as follows: the present invention is a pure metal catalyst for the synthesis of polyetheramines, which has higher structural strength and longer service life. The catalyst no longer requires an additional porous carrier, and has better catalytic activity. The catalyst of the present invention controls the pore volume to ensure that polyether polyols, liquid ammonia and hydrogen can flow smoothly through the pores on the catalyst surface, thereby improving the utilization rate of active ingredients. The catalyst of the present invention also adjusts the amount of alloy heavy metal components and adds a certain proportion of molybdenum and iron, which not only improves the selectivity and catalytic efficiency of the catalyst, but also makes the overall strength of the catalyst higher and the service life longer. The preparation process of the present invention can obtain alloy crystal phases with higher catalytic activity, and can avoid catalyst collapse during the etching of larger pores, thereby ensuring the skeleton strength of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 、 Figure 2 This is an electron microscope image of the iron-molybdenum-aluminum-nickel catalyst for polyetheramine synthesis of the present invention. DETAILED DESCRIPTION

[0030] The present invention will be further described below with reference to specific embodiments, wherein embodiment 1 is the best implementation.

[0031] Example 1

[0032] Prepare the metal powders of nickel, aluminum, molybdenum and iron in a mass ratio of 65.55﹕30﹕2.8﹕1.65; among them, nickel powder is 2μm~5μm, aluminum powder is 8μm~14μm, molybdenum powder is 5μm~8μm, and iron powder is 5μm~8μm.

[0033] 1) Heat the aluminum powder to 700℃ and melt it, then keep it warm for 300s. Then heat it to 1000℃ and add nickel powder. Stir it evenly with a carbon rod within 600s.

[0034] 2) The self-heating generated by the nickel dissolution was used to raise the furnace temperature by 260°C, and then the temperature was raised to 1455°C. The furnace was kept warm for 22 minutes while being purged with nitrogen.

[0035] 3) The melt is placed inside and outside a cooling tank and cooled by flowing cooling water, and cooled to room temperature within 300 seconds to obtain a nickel-aluminum alloy.

[0036] 4) The nickel-aluminum alloy is heated to 1455° C. and melted, and then molybdenum powder and iron powder are added and stirred evenly with a carbon rod within 600 seconds; the mixture is kept warm and smelted for 60 minutes while continuing to be purged with nitrogen, and then cooled to room temperature within 300 seconds to obtain an aluminum-nickel-molybdenum-iron alloy, i.e., a catalyst precursor.

[0037] 5) Crushing the catalyst precursor to obtain alloy particles of 10 mm to 25 mm, adding a 10 wt% aqueous sodium hydroxide solution to the alloy particles, with a mass ratio of the alloy particles to the sodium hydroxide contained therein being 5:1; gradually increasing the temperature from 10° C. to 105° C., reacting until no obvious bubbles emerge from the alloy particles, and then filtering.

[0038] 6) After filtering out the alloy particles, a 20 wt% aqueous sodium hydroxide solution is added, with the mass ratio of alloy particles to sodium hydroxide being 5:2. The temperature is gradually raised from 25° C. to 80° C., and the reaction is maintained until the alloy particles sink to the bottom and no obvious bubbles emerge. The filtered alloy particles are then rinsed four times with pure water, spray-washed until the pH of the water is neutral, and then rinsed three times with 95% ethanol. The resulting polyetheramine catalyst is stored in pure water or ethanol for future use.

[0039] Example 2

[0040] The metal powders of nickel, aluminum, molybdenum and iron are prepared in a mass ratio of 64:31:2.6:1.70; among them, nickel powder is 2μm~5μm, aluminum powder is 8μm~14μm, molybdenum powder is 5μm~8μm, and iron powder is 5μm~8μm.

[0041] 1) Heat the aluminum powder to 700℃ and melt it, then keep it warm for 350s. Then heat it to 1010℃ and add nickel powder. Stir it evenly with a carbon rod within 600s.

[0042] 2) The self-heating generated by the nickel dissolution was used to first raise the furnace temperature by 280°C, and then the temperature was raised to 1452°C. The furnace was kept warm for 24 minutes while being purged with nitrogen.

[0043] 3) The melt is placed inside and outside a cooling tank and cooled by flowing cooling water, and cooled to room temperature within 300 seconds to obtain a nickel-aluminum alloy.

[0044] 4) The nickel-aluminum alloy is heated to 1452° C. and melted, and then molybdenum powder and iron powder are added and stirred evenly with a carbon rod within 600 seconds; the mixture is kept warm and smelted for 58 minutes while continuing to be purged with nitrogen, and then cooled to room temperature within 300 seconds to obtain an aluminum-nickel-molybdenum-iron alloy, i.e., a catalyst precursor.

[0045] 5) Crushing the catalyst precursor to obtain alloy particles of 10 mm to 25 mm, adding an 11 wt% aqueous sodium hydroxide solution to the alloy particles, with a mass ratio of the alloy particles to the sodium hydroxide solution being 5:1.1; gradually increasing the temperature from 10° C. to 105° C., reacting until no obvious bubbles emerge from the alloy particles, and then filtering.

[0046] 6) After filtering out the alloy particles, a 21 wt% aqueous sodium hydroxide solution was added, with a mass ratio of alloy particles to sodium hydroxide of 5:2.2. The temperature was gradually raised from 25° C. to 80° C., and the reaction was maintained until the alloy particles settled to the bottom and no obvious bubbles emerged. The filtered alloy particles were rinsed four times with pure water and spray-washed until the pH of the water was neutral, and then rinsed three times with 95% ethanol by decantation. The resulting polyetheramine catalyst was stored in pure water or ethanol for future use.

[0047] Example 3

[0048] The metal powders of nickel, aluminum, molybdenum and iron are prepared in a mass ratio of 66:29:3.0:1.60; among them, nickel powder is 2μm~5μm, aluminum powder is 8μm~14μm, molybdenum powder is 5μm~8μm, and iron powder is 5μm~8μm.

[0049] 1) Heat the aluminum powder to 705℃ and melt it, then keep it warm for 280s. Then heat it to 995℃ and add nickel powder. Stir it evenly with a carbon rod within 600s.

[0050] 2) The self-heating generated by the nickel dissolution was used to raise the furnace temperature by 220°C, and then the temperature was raised to 1457°C. The furnace was kept warm for 20 minutes while being purged with nitrogen.

[0051] 3) The melt is placed inside and outside a cooling tank and cooled by flowing cooling water, and cooled to room temperature within 300 seconds to obtain a nickel-aluminum alloy.

[0052] 4) The nickel-aluminum alloy is heated to 1457° C. and melted, and then molybdenum powder and iron powder are added and stirred evenly with a carbon rod within 600 seconds; the mixture is kept warm and smelted for 62 minutes while continuing to be purged with nitrogen, and then cooled to room temperature within 300 seconds to obtain an aluminum-nickel-molybdenum-iron alloy, i.e., a catalyst precursor.

[0053] 5) Crushing the catalyst precursor to obtain alloy particles of 10 mm to 25 mm, adding a 9 wt % aqueous sodium hydroxide solution to the alloy particles, with a mass ratio of the alloy particles to the sodium hydroxide solution being 5:0.9; gradually increasing the temperature from 10° C. to 105° C., reacting until no obvious bubbles emerge from the alloy particles, and then filtering.

[0054] 6) After filtering out the alloy particles, a 19 wt% aqueous sodium hydroxide solution was added, with a mass ratio of alloy particles to sodium hydroxide of 5:1.9. The temperature was gradually raised from 25° C. to 80° C., and the reaction was maintained until the alloy particles settled to the bottom and no obvious bubbles emerged. The filtered alloy particles were rinsed four times with pure water and spray-washed until the pH of the water was neutral, and then rinsed three times with 95% ethanol by decantation. The resulting polyetheramine catalyst was stored in pure water or ethanol for future use.

[0055] Example 4

[0056] The metal powders of nickel, aluminum, molybdenum and iron are prepared in a mass ratio of 62:33:2.3:1.85; the nickel powder is 2μm to 5μm, the aluminum powder is 8μm to 14μm, the molybdenum powder is 5μm to 8μm, and the iron powder is 5μm to 8μm.

[0057] 1) Heat the aluminum powder to 695℃ and keep it warm for 400s. Then heat it to 990℃ and add nickel powder. Stir it evenly with a carbon rod within 600s.

[0058] 2) The furnace temperature was first raised by 200°C by self-heating generated by nickel dissolution, and then heated to 1449°C. The furnace was kept warm for 26 minutes while being purged with nitrogen.

[0059] 3) The melt is placed inside and outside a cooling tank and cooled by flowing cooling water, and cooled to room temperature within 300 seconds to obtain a nickel-aluminum alloy.

[0060] 4) The nickel-aluminum alloy is heated to 1449° C. and melted, and then molybdenum powder and iron powder are added and stirred evenly with a carbon rod within 600 seconds; the mixture is kept warm and smelted for 65 minutes while continuing to be purged with nitrogen, and then cooled to room temperature within 300 seconds to obtain an aluminum-nickel-molybdenum-iron alloy, i.e., a catalyst precursor.

[0061] 5) Crushing the catalyst precursor to obtain alloy particles of 10 mm to 25 mm, adding an 8 wt % aqueous sodium hydroxide solution to the alloy particles, with a mass ratio of the alloy particles to the sodium hydroxide solution being 5:0.8; gradually increasing the temperature from 10° C. to 105° C., reacting until no obvious bubbles emerge from the alloy particles, and then filtering.

[0062] 6) After filtering out the alloy particles, an 18 wt% aqueous sodium hydroxide solution was added, with a mass ratio of alloy particles to sodium hydroxide of 5:1.7. The temperature was gradually raised from 25° C. to 80° C., and the reaction was maintained until the alloy particles settled to the bottom and no obvious bubbles emerged. The filtered alloy particles were rinsed four times with pure water and spray-washed until the pH of the water was neutral, and then rinsed three times with 95% ethanol by decantation. The resulting polyetheramine catalyst was stored in pure water or ethanol for future use.

[0063] Example 5

[0064] The metal powders of nickel, aluminum, molybdenum and iron are prepared in a mass ratio of 68:27:3.3:1.45; the nickel powder is 2μm to 5μm, the aluminum powder is 8μm to 14μm, the molybdenum powder is 5μm to 8μm, and the iron powder is 5μm to 8μm.

[0065] 1) Heat the aluminum powder to 710℃ and melt it, then keep it at this temperature for 270s. Then heat it to 1020℃ and add nickel powder. Stir it evenly with a carbon rod within 600s.

[0066] 2) The furnace temperature was first raised by 300°C by self-heating generated by nickel dissolution, and then heated to 1459°C. The furnace was kept warm for 18 minutes while being purged with nitrogen.

[0067] 3) The melt is placed inside and outside a cooling tank and cooled by flowing cooling water, and cooled to room temperature within 300 seconds to obtain a nickel-aluminum alloy.

[0068] 4) The nickel-aluminum alloy is heated to 1459° C. and melted, and then molybdenum powder and iron powder are added and stirred evenly with a carbon rod within 600 seconds; the mixture is kept warm and smelted for 55 minutes while continuing to be purged with nitrogen, and then cooled to room temperature within 300 seconds to obtain an aluminum-nickel-molybdenum-iron alloy, i.e., a catalyst precursor.

[0069] 5) Crushing the catalyst precursor to obtain alloy particles of 10 mm to 25 mm, adding a 13 wt% aqueous sodium hydroxide solution to the alloy particles, with a mass ratio of the alloy particles to the sodium hydroxide solution being 5:1.3; gradually increasing the temperature from 10° C. to 105° C., reacting until no obvious bubbles emerge from the alloy particles, and then filtering.

[0070] 6) After filtering out the alloy particles, a 23 wt% aqueous sodium hydroxide solution was added, with a mass ratio of alloy particles to sodium hydroxide of 5:2.4. The temperature was gradually raised from 25° C. to 80° C., and the reaction was maintained until the alloy particles settled to the bottom and no obvious bubbles emerged. The filtered alloy particles were rinsed four times with pure water and spray-washed until the pH of the water was neutral, and then rinsed three times with 95% ethanol by decantation. The resulting polyetheramine catalyst was stored in pure water or ethanol for future use.

[0071] Comparative Example 1

[0072] The proportions and process conditions were the same as in Example 1, except that no iron powder was added.

[0073] Comparative Example 2

[0074] The proportions and process conditions are the same as those in Example 1, except that the metal powders of nickel, aluminum, molybdenum and iron are directly smelted together at 1455° C. for 80 minutes.

[0075] Comparative Example 3

[0076] The proportions and process conditions were the same as those in Example 1, except that the obtained alloy particles were directly treated with a 20 wt % sodium hydroxide aqueous solution.

[0077] The catalytic performance test process of the catalysts obtained in each example is unified as follows: 80 mL of the catalyst prepared in the example is loaded into a fixed-bed continuous flow reactor, a portion of liquid ammonia is pumped in, the reactor temperature is raised to 180°C, and hydrogen is pumped in to raise the reactor pressure to 13.5 MPa; then, after the reaction system is stable, the polyether polyol space velocity is 0.5 h -1 , the molar ratio of liquid ammonia to polyether polyol is 14:1, and the molar ratio of hydrogen to polyether polyol is 1:1; then, the material is discharged after 24 hours of continuous and stable reaction, and the crude product is filtered, vacuum rotary distilled and dehydrated to obtain polyetheramine. The total amine value is measured and the conversion rate of the polyetheramine in this example is calculated.

[0078] Weight loss: The catalyst life is determined by placing 20g of catalyst on a rotating drum at 500 rpm for 1 hour and measuring the weight loss of the catalyst solid. The smaller the weight loss, the longer the catalyst life.

[0079] The catalyst has a pore volume of 0.051 m2 / g to 0.055 m2 / g, a bulk density of 1.95 g / ml to 2.13 g / ml, a nickel content of 55 wt% to 75 wt%, an aluminum content of 23.8 wt% to 42 wt%, a molybdenum content of 0.6 wt% to 1.5 wt%, and an iron content of 0.6 wt% to 1.5 wt%. The crystallite diameter is 1 nm to 3 nm, the catalyst has a skeletal strength of 161 N / cm to 168 N / cm, and the catalyst specific surface area is controlled within a range of 10 m2 / g to 30 m2 / g. The performance test results of the embodiments are shown in Table 1. The balance of the nickel, aluminum, and molybdenum contents in Table 1 for each catalyst composition is the iron content and trace impurities.

[0080] Table 1

[0081]

[0082] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other manner. Any person skilled in the art may utilize the above-disclosed technical content to modify or modify the present invention into equivalent embodiments. However, any simple modifications, equivalent variations, and modifications to the above embodiments that do not depart from the technical content of the present invention and are based on the technical essence of the present invention remain within the scope of protection of the present invention.

Claims

1. A process for preparing an iron-molybdenum-aluminum-nickel catalyst for the synthesis of polyetheramines, characterized in that: The process steps are: Prepare nickel, aluminum, molybdenum and iron metal powders in a mass ratio of 62-68:27-33:2.3-3.3:1.45-1.85; 1) Heat the aluminum powder to 695℃~710℃ to melt and keep it warm for 270s~400s, then heat it to 990℃~1020℃ and add nickel powder, and stir it evenly with a carbon rod within 600s; 2) Using the self-heating generated by nickel dissolution to raise the furnace temperature by 200°C to 300°C, then heating to 1449°C to 1459°C, and keeping the temperature for 18min to 26min; 3) Cooling the melt to room temperature within 300 seconds to obtain a nickel-aluminum alloy; 4) heating the nickel-aluminum alloy to 1449° C. to 1459° C., melting the alloy, adding molybdenum powder and iron powder, and stirring the alloy evenly with a carbon rod within 600 seconds; continuing to heat and melt for 55 to 65 minutes, and cooling the alloy to room temperature within 300 seconds to obtain an aluminum-nickel-molybdenum-iron alloy, i.e., a catalyst precursor; 5) crushing the prepared catalyst precursor to obtain alloy particles, adding 8wt% to 13wt% sodium hydroxide aqueous solution to the alloy particles, controlling the temperature to gradually increase from 10°C to 105°C, reacting until no obvious bubbles emerge from the alloy particles, and filtering; 6) After filtering out the alloy particles, adding 18 wt% to 23 wt% sodium hydroxide aqueous solution, and gradually raising the temperature from 25° C. to 80° C., and maintaining the reaction until the alloy particles sink to the bottom and no obvious bubbles emerge, filtering and washing the alloy particles to obtain a catalyst for polyetheramine; The obtained catalyst is a metal alloy of nickel, aluminum, molybdenum and iron. The nickel content of the catalyst is 77.3wt% to 80.7wt%, the aluminum content is 13.6wt% to 17.7wt%, the molybdenum content is 2.9wt% to 3.9wt%, and the iron content is 1.2wt% to 2.6wt%.

2. The process for preparing an iron-molybdenum-aluminum-nickel catalyst for synthesizing polyetheramines according to claim 1, characterized in that: The mass ratio of the nickel, aluminum, molybdenum and iron metal powders is 64-66:29-31:2.6-3.0:1.60-1.

70.

3. The process for preparing an iron-molybdenum-aluminum-nickel catalyst for synthesizing polyetheramines according to claim 1, characterized in that: The particle sizes of the metal powders are: nickel powder 2μm-5μm, aluminum powder 8μm-14μm, molybdenum powder 5μm-8μm, and iron powder 5μm-8μm.

4. The process for preparing an iron-molybdenum-aluminum-nickel catalyst for synthesizing polyetheramines according to claim 1, characterized in that: The cooling methods described in step 3) and step 4) are both to place the melt inside or outside a cooling tank and cool it down using flowing cooling water.

5. The process for preparing an iron-molybdenum-aluminum-nickel catalyst for synthesizing polyetheramines according to claim 1, characterized in that: During the heat preservation smelting described in step 2) and step 4), nitrogen purging is used throughout the whole process.

6. The process for preparing an iron-molybdenum-aluminum-nickel catalyst for the synthesis of polyetheramines according to claim 1, characterized in that: The alloy particles obtained in step 5) are irregular particles with a particle size of 10 mm to 25 mm.

7. The process for preparing an iron-molybdenum-aluminum-nickel catalyst for synthesizing polyetheramines according to claim 1, characterized in that: The mass ratio of the alloy particles in step 5) to the sodium hydroxide contained in the sodium hydroxide aqueous solution is 5:0.8-1.3; the mass ratio of the alloy particles in step 6) to the sodium hydroxide contained in the sodium hydroxide aqueous solution is 5:1.7-2.

4.

8. The process for preparing an iron-molybdenum-aluminum-nickel catalyst for synthesizing polyetheramines according to claim 1, characterized in that: The washing in step 6) specifically comprises decantation washing the filtered alloy particles with pure water for four times, spray washing until the pH of the water is neutral, and then decantation washing with 95% ethanol for three times; the obtained polyetheramine catalyst is stored in pure water or ethanol for standby use.

Citation Information

Patent Citations

  • Polyether amine as well as preparation method and application thereof

    CN116284738A

  • Supported catalyst used for synthesizing polyether amine, preparation method, and application

    US20230174714A1

  • High-activity nickel-aluminum alloy hydrogenation catalyst and preparation method thereof

    CN115193443A